Case Report: Clinical and Serological Hallmarks of Cytokine Release Syndrome in a Canine B Cell Lymphoma Patient Treated With Autologous CAR-T Cells - Atherton, Matthew J.; Rotolo, Antonia; Haran, Kumudhini P.; Mason, Nicola J. (Frontiers in Veterinary Science, 2022)
Background: Chimeric antigen receptor-T (CAR-T) cells have transformed the treatment of human B cell malignancies. With the advent of CAR-T therapy, specific and in some cases severe toxicities have been documented with cytokine release syndrome (CRS) being the most frequently reported. As dogs develop tumors spontaneously and in an immunocompetent setting, they provide a unique translational opportunity to further investigate the activity and toxicities associated with CAR-T therapy. Although various adoptive cellular therapy (ACT) trials have been documented and several more are ongoing in canine oncology, CRS has not been comprehensively described in canine cancer patients. Case presentation: Here we present the clinical and serologic changes in a dog treated with autologous CAR-T for relapsed B cell lymphoma that presented with lethargy and fever three days following CAR-T. Multiplexed serum cytokine profiling revealed increases in key cytokines implicated in human CRS including IL-6, MCP-1, IFNγ and IL-10 at or shortly after peak CAR-T levels in vivo. Conclusion: The observations noted in this case report are consistent with CRS development following CAR-T therapy in a canine patient. The dog represents a compelling model to study the pathophysiology of CRS and pre-clinically screen novel therapeutics to prevent and treat this life-threatening condition in the setting of a complex and naturally evolved immune system.